Nye medier - ny journalistik? En pilotundersøgelse af netnyhedsproduktionen i Danmark - Hartley, Janni Møller (Journalistica, 2009)
Based on a pilot study this article examines the research hypotheses in the field of online-journalism, with particular focus on the Nordic literature. It argues that the growth of online journalism and online newspapers is not necessarily the case of new kind of journalism; on the one hand, the pilot study confirms a blurring of the relationship between journalists and readers, and a change in the form of continuous real-time editing and publishing. Yet it appears that many of the characteristics of online journalism are well known, and thus, the development might rather be seen as a radicalisation of some traditional journalistic routines in the production of news. A radicalization that indicates that news in the Digital Age can be seen as a dynamic process rather than a static product.